Wolves are better imitators of conspecifics than dogs. - Friederike Range; Zsófia Virányi (PLoS ONE)
Domestication is thought to have influenced the cognitive abilities of dogs underlying their communication with humans, but little is known about its effect on their interactions with conspecifics. Since domestication hypotheses offer limited predictions in regard to wolf-wolf compared to dog-dog interactions, we extend the cooperative breeding hypothesis suggesting that the dependency of wolves on close cooperation with conspecifics, including breeding but also territory defense and hunting, has created selection pressures on motivational and cognitive processes enhancing their propensity to pay close attention to conspecifics' actions. During domestication, dogs' dependency on conspecifics has been relaxed, leading to reduced motivational and cognitive abilities to interact with conspecifics. Here we show that 6-month-old wolves outperform same aged dogs in a two-action-imitation task following a conspecific demonstration. While the wolves readily opened the apparatus after a demonstration, the dogs failed to solve the problem. This difference could not be explained by differential motivation, better physical insight of wolves, differential developmental pathways of wolves and dogs or a higher dependency of dogs from humans. Our results are best explained by the hypothesis that higher cooperativeness may come together with a higher propensity to pay close attention to detailed actions of others and offer an alternative perspective to domestication by emphasizing the cooperativeness of wolves as a potential source of dog-human cooperation.